Comparison between Mammography and Breast Ultrasound in the Detection of Breast Cancer in Dense Breast Tissue among a Sample of Iraqi Women - Abdulwahid, hiba mohammed (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Breast cancer is the most common cancer reported in women worldwide . In Iraq, it is the most common registered malignancy. Mammography plays a major role in the early detection of breast cancers. Dense breast parenchyma has been reported to be the most important inherent factor that limits depiction of breast cancer on mammogram, and often needs supplementary breast ultrasound for complete assessment. Objectives: To evaluate and compare the diagnostic performance of mammography and ultrasound in the detection of breast cancer in dense breast tissue. Patients and methods: A record review study was performed in the Oncology Teaching Hospital/ Medical City from April 2018 to December 2018. The study included forty five females, who attended the Main Referral Center for Early Detection of Breast Tumors during 2017 and 2018 were diagnosed with breast cancer histopathologically . They had dense breast tissues on mammography (either heterogeneously dense breast tissue i.e . category C or extremely dense breast tissue i.e. category D). All patients underwent subsequent breast ultrasound . Their information including the mammogram findings, breast ultrasound, fine needle aspiration (FNA) and biopsy results were reviewed analyzed and compared. Results:Twenty four patients (53.3%) had heterogeneously dense breast tissue (ACR category C) and 21 patients (46.6%) had extremely dense breast tissue (ACR category D). The mammogram detected 36 from 45 breast cancers (80%) while 9 (20%) were not detected by mammogram, so the mammogram had a detection rate of breast cancer of 80% in mammographically dense breast, while breast ultrasound had higher detection rate of about 97.7% .The sensitivity of mammography in extremely dense breast tissue was about 71% and in heterogeneously dense breast was about 87% while ultrasound had shown a higher sensitivity with increasing tissue density (98% vs. 100%). Conclusion: Breast cancer can be easily obscured and missed in mammographically dense breast tissue due to overlapping surrounding fibroglandular tissue and additional complementary breast ultrasound is highly recommended for a thorough evaluation and to depict mammographically occult breast carcinoma.